Disseminated histoplasmosis and hemophagocytic lymphohistiocytosis in a patient receiving TNF-alpha inhibitor therapy. (2022) - Zhong, Qiaonan; Ordaya, Eloy E.; Fernandez, Santiago Delgado; Lescalleet, Kristin; Larson, Daniel; Pritt, Bobbi; Berbari, Elie
Abstract: Histoplasmosis commonly presents as an asymptomatic or self-limited infection in immunocompetent patients, but immunocompromised hosts may present with severe and disseminated disease. Herein, we present a 26-year-old male with history of ulcerative colitis receiving long-term TNF-alpha inhibitor therapy who presented with six months of diarrhea and recently fever and hematochezia. On admission, he was febrile and hypotensive, with initial workup revealing pancytopenia and imaging reporting pulmonary infiltrates, pancolitis, and enlarged mesenteric lymph nodes. Disseminated histoplasmosis was ultimately diagnosed after examination of the colonic biopsy. Bone marrow biopsy was also consistent with the diagnosis of histoplasmosis but also demonstrated hemophagocytic lymphohistiocytosis. The patient was ultimately treated with amphotericin B, intravenous immunoglobulin, etoposide, and corticosteroids.